STOCK MARKET INDICATORS AND NIGERIAN ECONOMY - Adekunle, Adewale Abass; Adeyinka, Adewole Joseph (Universitas Jember, 2024)
ABSTRACTThis study examines the impact of stock market indicators on economic growth in Nigeria. The research used an expo-facto design and purposive sampling, employing ARDL to analyze the effects of stock market indicators on Nigeria's economic growth. Data was sourced from Central Bank of Nigeria Statistical Bulletin. The overall findings revealed correlation value of 0.628 which indicate a moderate positive correlation between the predictors Equity (LEQ), Corporate Bond (LCB), All-Share Index (LALS), and Inflation (INFLA) and GDP. The study also revealed F statistic of 4.237 with a significance level of 0.009 which confirms that the model is statistically significant, meaning that there is significant relationship between the dependent and independent variables. The study recommendations that the policymaker should not only rely on the value of bond as the driver on economic growth in Nigeria. The investors can be encouraged to diversify their investment across different asset classes which serve as long-term investment strategy rather than focusing on the stock market equities. This is because the economic cycle and market trend can change over time and this will mitigate risk that is associated with volatile equity market and take into account broader economic trend and potential growth over time. The Nigeria stock market regulators should always review rules and regulations guiding the activities of buying and selling on the market in order to promote efficiency in price movement of stock market.Keywords: All Share Indexes; Gross Domestic Product; Stock Market Corporate Bonds; Stock Market Equities.